AD, Volume 18, n° 2, 1993 - Full Issue - Journal System, (Africa Development, 1993)
Contents Some Problems in Ghana's Transition to Democratic Governance Kwame A Ninsin ............................. 5 Angolan Woman and the Electoral Process in Angola, 1992 Horace Campbel .......................... 23 Safeguarding Human Rights: A Critique of the African Commission on Human and People's Rights Kofi Oteng Kufuor ........................... 65 Entreprises étrangères et activités industrielles en Afrique de l'Ouest Amadou Kaka .............................. 79 Sustainable Development in the African Context: Revisiting Some Theoretical and Methodological Issues George J S Dei .............................. 97 Contribution à l'analyse essentielle de la tontine africaine Jean-Roger Essombe-Edimo ...................... 111 Book Reviews Samir Amin, Le tiers monde entre les impératifs de la mondialisation et les nécessités de l'autonomie - Quelques remarques autour de l'empire du chaos Hamid Ait Amara & Hakim Ben Hammouda ............... 123 Gabon: Beyond the Colonial Legacy Jerry Komia Domatob ................... 128 Publication received ......................... 133